Maximum power point tracking-based hybrid pulse width modulation for harmonic reduction in wind energy conversion systems. (September 2020) - Boopathi, R.; Jayanthi, R.; Ansari, M. Mohamed Thameem
Abstract: Reduction of total harmonic distortion (THD) in fundamental output voltage and current in wind energy conversion systems (WECS) is the primary objective of this research paper. Reduction of distortion effects help in regulating the output voltage to a great extent. The paper suggests a novel perturb-and-observe (P&O)-based maximum power point tracking (MPPT) for the front-end single-ended primary-inductor converter (SEPIC), in an effort to exploit the maximum power from the available wind source. It further involves a hybrid space vector pulse width modulation (HSVPWM) scheme for generating the pulses to switches in the voltage source inverter (VSI), to improve the quality of the output AC power. It examines the performance through simulation in the MATLAB platform over a range of operating loads to illustrate the benefits of the scheme, in terms of a lower THD. The experimental results obtained from a prototype serve to validate the simulated response and claim its suitability for use in real world applications.